The Policy of Honoris Causa Doctorate in Indonesian Higher Education 2000-2020 - Moh Mudzakkir; Mohammad Reevany Bustami; Ikomatussuniah Ikomatussuniah; Wani Maler (Universitas Muhammadiyah Yogyakarta, 2021)
This article examines the conferring of honorary doctorates in Indonesian universities, which has increased significantly in the last twenty years, 2000-2020. This research applies the document analysis method; data obtained from public documents from government, universities, magazines, and newspapers. Normatively, the university conferred the Doctor Honoris Causa to individuals with outstanding service or work and contributed to science, technology, culture, humanity, and society. The study reveals that the Indonesian authorities have issued three amended regulations regarding honorary doctorates between 2000-2020. This policy provides increased flexibility to universities in determining the awarding of honorary degrees compared to previous regulations. This research has uncovered an evolutionary trajectory of shifting away from awarding the honorary doctorates to the academic community towards non-academic and even political circles and public officials. Such a policy or practice invites criticisms that this signifies an exchange of interests between campus leaders and the power establishment in Indonesia. The analysis of this research reveals that with the decentralization of power during the post-reformation era, there is a transformation of institutional logic of higher education from recognizing knowledge advancement and scientific contributions of members of intelligentsia towards empowering the legitimacy of ruling establishments, especially among politicians and powerful public officials.